2020
DOI: 10.1186/s12936-020-03475-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between recent overnight travel and use of long-lasting insecticidal nets in rural Uganda: a prospective cohort study in Tororo

Abstract: Background The burden of malaria in Uganda remains high, but has become increasingly heterogenous following intensified malaria control. Travel within Uganda is recognized as a risk factor for malaria, but behaviours associated with travel are not well-understood. To address this knowledge gap, malaria-relevant behaviours of cohort participants were assessed during travel and at home in Uganda. Methods Residents from 80 randomly selected households in Nagongera sub-county, Tororo district were enrolled into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Gender differences were observed in the use of LLINs in lodging places, with females less likely to use those considered of poor quality and unhygienic, compared to males who seemed not to mind. This is consistent with a study conducted in Uganda that showed that women were less likely than men to sleep under LLINs during travel [ 24 ]. The negative perception and cultural beliefs community members held about people who used LLINs, especially during social events, hindered their use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gender differences were observed in the use of LLINs in lodging places, with females less likely to use those considered of poor quality and unhygienic, compared to males who seemed not to mind. This is consistent with a study conducted in Uganda that showed that women were less likely than men to sleep under LLINs during travel [ 24 ]. The negative perception and cultural beliefs community members held about people who used LLINs, especially during social events, hindered their use.…”
Section: Discussionsupporting
confidence: 92%
“…Within sub-Saharan Africa, travellers from areas of lower to higher transmission intensity are potentially at high risk of malaria infection and yet use of LLINs during travel is limited [ 24 ]. In this urban population, perceptions, attitudes and experiences were explored regarding use of LLINs for malaria prevention by Kampala residents travelling to other parts of Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…in 2012, 4 has materialized into three serial universal LLIN coverage campaigns since 2013, and NMCD has provided platforms and collaborated with PRISM to ensure evaluation of these campaigns. 6 , 49 The LLINEUP and LLINEUP2 cluster-randomized trials provide substantive evidence that NMCD values and supports use of locally generated research findings to inform planning and design of each universal LLIN campaign. 6 , 49 Preliminary work done in preparation for the LLINEUP2 study entailed demonstration of the feasibility of using routine health facility–based surveillance data to generate malaria incidence estimates.…”
Section: Support To Malaria Control Efforts Through Enhanced Health F...mentioning
confidence: 79%
“…Low perceived risk has been previously documented as a potential barrier to LLIN use [ 45 ]. While staff did not assess travel histories or perform entomologic surveillance [ 46 , 47 ], it is possible that some, if not most, of the infections identified at higher elevations may have been acquired during travel to lower-elevation market areas or social events (i.e., church, weddings). Given the lower prevalence of infection and minimal expected effect of LLINs on travel-related risk, these findings suggest that, at least from an economic standpoint, LLIN distribution at higher altitudes may be an inefficient use of resources.…”
Section: Discussionmentioning
confidence: 99%